1998
DOI: 10.1103/physrevb.58.3371
|View full text |Cite
|
Sign up to set email alerts
|

Layered (Cu,Fe) oxides of double perovskite structure: Correlation between structural and magnetic-property changes inBaY(Cu0.5

Abstract: In this paper, we report the correlation between the magnetic property and the local structure in BaY͑Cu 0.5 Fe 0.5 ͒ 2 O 5ϩ␦ of the ''0112'' phase containing an unusually large amount of excess oxygen, ␦ of ϳ0.2, when heat treated under a high pressure of 5 GPa. Magnetic susceptibility measurements showed that upon the high-pressure heat treatment, the lower-temperature magnetic transition which had been observed in normal-pressure synthesized, antiferromagnetic BaY͑Cu 0.5 Fe 0.5 ͒ 2 O 5 disappeared and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The same two components were also identified in the recent studies 18,19 of the Y(Ba,La)(Cu 0.5ϩx Fe 0.5Ϫx ) 2 O 5ϩw double perovskites with trivalent iron. When w decreases below 0.5, signatures of increasing amounts of Fe 2ϩ are found.…”
Section: Cn6mentioning
confidence: 53%
“…The same two components were also identified in the recent studies 18,19 of the Y(Ba,La)(Cu 0.5ϩx Fe 0.5Ϫx ) 2 O 5ϩw double perovskites with trivalent iron. When w decreases below 0.5, signatures of increasing amounts of Fe 2ϩ are found.…”
Section: Cn6mentioning
confidence: 53%
“…Fe> species in the intermediate spin state are not considered here, as the excess oxygen present in the phase indicates that oxidized Fe species should be found. In the earlier reports only one such component was detected (4,5,9) Table 3. The total amount of oxidized Fe in the MoK ssbauer spectra remains roughly the same, whether one is "tting the spectra using one or two components.…”
Section: Resultsmentioning
confidence: 86%
“…Thus, one is tempted to equate this component with the satellite of Component 1. However, one additional component, seen mainly in high-pressure treated Y-based samples has been reported (5,9). It has an isomer shift typical of Fe> and reaches its saturation "eld of more than 50 T already at 300 K and can thus hardly be considered a satellite of Component 1.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Ruiz-Aragon [3], the space group of this compound is P 4/ mmm . Magnetic and Mössbauer effect measurements indicate that the Fe ions in YBaCuFeO 5 undergo antiferromagnetic ordering at 460 [1], 446 [2], or 440 K [4]. Detailed studies of the magnetic structure of YBaCuFeO 5 revealed several magnetic phase transitions [3], two of which were identified as paramagnetic antiferromagnetic I (near 475 K) and antiferromagnetic I antiferromagnetic II (near 240 K) transitions.…”
Section: Introductionmentioning
confidence: 99%